Belief aggregation in financial markets and the nature of price fluctuations - Schoch, Daniel (Springer International Publishing, 2015)
We present a model of financial markets, where the belief of the market, expressed by a normal distribution over asset returns, is formed by aggregating in a dynamically consistent way individual subjective beliefs of the market participants, which are likewise assumed to follow normal distributions. We apply this model to a market of traders with standard CARA preferences with the aim of identifying an intrinsic source of price fluctuations. We find that asset prices depend on both Gaussian parameters mean and variance of the market belief, but argue that the latter changes slower than the former. Consequently, price fluctuations are dominated by the covariance matrix of the market participants’ subjective beliefs about expected asset returns.